THE URGENCY OF THE HEAD OF VILLAGE’S EXTENSION FROM LEGAL PERSPECTIVE AND DEMOCRATIC THEORY - Syafwar, Robi; Marwenny, Elwidarifa; Utama, Bobby Setia (JCH (Jurnal Cendekia Hukum), 2023)
The Head of Village’s office work of only six years is considered too short, so elected village heads often do not have enough time to complete development plans in their villages. It is hoped that extending the Village Head's term of office to 9 years will increase the effectiveness of development and community welfare. On the other hand, extending the term of office is considered inconsistent with the spirit of democracy and the principles of the rule of law. This research aims to find out the legal regulations related to the position of village head and the urgency of extending the work of village head from a legal perspective and democratic theory. The author utilizes qualitative research methods with a normative juridical approach to explain the questions asked. The development of policies governing the term of office of village heads in Indonesia reflects changes in the structure of the village government. The discourse on increasing the term of office of village heads to nine years raises profound questions about the balance between leadership stability and the essence of democracy in the context of village government in Indonesia. Extending the term of office of village heads is not in line with the spirit of democracy and can open up space for developing oligarchy at the village level. Limiting power and limiting terms of office are the main principles for preventing abuse and maintaining balance in government.